Correlation of Hematologic Indices with CT-pulmonary Arterial Obstruction Index in Patients with Acute Pulmonary Emboli - Faghihi Langhroudi, Taraneh; Borji Esfahani, Mahtab; Khaheshi, Isa; Naderian, Mohammadreza; Zahedi Tajrishi, Farbod; Namazi, Mohammad Javad (International Journal of Cardiovascular Practice, 2019)
Introduction: Acute Pulmonary thromboembolism (PTE) is an imperative medical condition with a considerable global impact. Inflammation is deemed to take a notable part in the pathophysiology of this potentially fatal disorder. The aim of the current study was to predict acute PTE severity in helical pulmonary CT-angiography using easily accessible hematological complete blood count (CBC) indices.Methods: After exclusion of inflammatory conditions that may affect CBC parameters, a total of 69 consecutive patients with definite diagnosis of acute PTE according to pulmonary helical CT ?angiography were recruited. Laboratory tests, including CBC parameters were performed on admission in the emergency unit, before initiation of any therapy. Neutrophil to lymphocyte ratio (NLR), platelet to lymphocyte ratio (PLR) and RDW to platelet ratio (RPR) were calculated in each case of acute PTE. Ultimately, CT pulmonary arterial obstruction index (PAOI) was assessed subsequent to pulmonary helical CT-angiography for each patient.Results: We found that NLR is positively correlated with acute PTE severity according to CT pulmonary arterial obstruction index (PAOI) (P < 0.01, r = 0.56); however, PLR, RDW and RPR did not appear to show such correlations (P > 0.05).Conclusions: NLR could be an easily calculated and capable index to predict severity of acute PTE in pulmonary CT-angiography. Consequently, NLR might be used in precise risk stratification when suspicious for acute PTE and in accurately triage of patients who would benefit greatly from urgent diagnostic and therapeutic interventions.